PERCEPTION OF RELIGIOUS FESTIVALS ACROSS GENERATIONS AND ITS IMPACT ON THE YOUTH VALUE - Ghosh, Payel Dey; Khurana, Divyani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Religious festivals are an integral part of Indian culture. However, the meaning, concept, and essence of the celebration of these festivals are different for different people. The present research attempts to assess how the perception of religious festivals changes across generations and its impact on the value system of youths. The research was conducted on a sample of 20 (male 9 and female 11) individuals from the age range of 20 to 70. The sample was further divided into 4 age groups: 59 to 70 years (n=5), 43 to 58 years (n=5), 27 to 42 years (n=5), and 20 to 26 years (n=5). In the present study, data were collected through semi-structured interviews and thematically analysed. Finding revealed significant variation in the perception of the essence of religious festivals across generations. Spirituality, community welfare, and interpersonal connections are essential for older generation groups. However, the younger generation’s perception is much more individualized. Thus, indicating towards changes in value system regarding to aging.